A review on in situ phytoremediation of mine tailings. (October 2017) - Wang, Li; Ji, Bin; Hu, Yuehua; Liu, Runqing; Sun, Wei
Abstract: Mine tailings are detrimental to natural plant growth due to their physicochemical characteristics, such as high pH, high salinity, low water retention capacity, high heavy metal concentrations, and deficiencies in soil organic matter and fertility. Thus, the remediation of mine tailings has become a key issue in environmental science and engineering. Phytoremediation, an in situ cost-effective technology, is emerging as the most promising remediation method for mine tailings by introducing tolerant plant species. It is particularly effective in dealing with large-area mine tailings with shallow contamination of organic, nutrient and metal pollutants. In this review, the background, concepts and applications of phytoremediation are comprehensively discussed. Furthermore, proper amendments used to improve the physical, chemical and biological properties of mine tailings are systematically reviewed and compared. Emphasis is placed on the types and characteristics of tolerant plants and their role in phytoremediation. Moreover, the role of microorganisms and their mechanism in phytoremediation are also discussed in-depth. Highlights: Mine tailings pose significant risk to the environment. Reviewed the development of mine tailing remediation techniques. Concept of phytoremediation of mine tailings is presented. Factors affecting phytoremediation of mine tailings are discussed.